Integrating Turkish Work and Achievement Goals With Schwartz's Human Values - ÇİNKO, MURAT; TURGUT, TÜLAY (PSYCHOPEN, 2015)
The purpose of this study was to examine the integration of indigenous values developed in Turkey to Schwartz's universal values. Students (N = 593) from six universities in Istanbul responded the value scale, which consists of 10 etic PVQ items (each item representing one of 10 main Schwartz values) and 23 emic WAG items (representing work-achievement goals). PROXSCAL, a multidimensional scaling method, was used to test whether etic and emic sets of values integrate and form the universal circular structure proposed in Schwartz value theory. The motivational continuum of values as a circular structure was similar to pan-cultural results, but adding another value type to the openness to change pole. While some of the items in this region represent autonomy of thought, remaining items diverge. The principle of conflicting values on opposite poles was not supported in relation to openness to change-conservation dimension. These two poles had similar priorities, contrasting with pan-cultural results, and demonstrating a culture-specific aspect of responding to motivational goals. Insights gained by emic studies will be functional in enriching understanding values, and contributing to the comprehensiveness and universality of Schwartz value theory.
Keywords: basic human values; emic studies; work goal; achievement goal; intrinsic motivation; SELF-DETERMINATION THEORY; BEHAVIOR; MOTIVATION; COUNTRIES